The Four FAD-Dependent Histone Demethylases of Arabidopsis Are Differently Involved in the Control of Flowering Time - Martignago, Damiano; Bernardini, Benedetta; Polticelli, Fabio; Salvi, Daniele; Cona, Alessandra; Angelini, Riccardo; Tavladoraki, Paraskevi (Frontiers in Plant Science, 2019)
In Arabidopsis thaliana, four FAD-dependent lysine-specific histone demethylases (LDL1, LDL2, LDL3 and FLD) are present, bearing both a SWIRM and an amine oxidase domain. In this study, a comparative analysis of gene structure, evolutionary relationship, tissue- and organ-specific expression pattern, physiological roles and target genes for the four Arabidopsis LDL/FLDs is reported. Phylogenetic analysis evidences a different evolutionary history for the four LDL/FLDs, while promoter activity data show that LDL/FLDs are strongly expressed in rapidly dividing tissues during seedling development and throughout embryogenesis, with some gene-specific expression patterns. Furthermore, phenotypical analysis of loss-of-function mutants indicate a role of all four Arabidopsis LDL/FLD genes in the control of flowering time, though for some of them with opposing effects. This study makes a contribution towards a better understanding of the LDL/FLD physiological roles and may provide biotechnological strategies for crop improvement.